Worms in the sand: Systematic revision of the Australian blindsnake Anilios leptosoma (Robb, 1972) species complex (Squamata: Scolecophidia: Typhlopidae) from the Geraldton Sandplain, with description of two new species - Ellis, Ryan J.; Doughty, Paul; Donnellan, Stephen C.; Marin, Julie; Vidal, Nicolas (Zootaxa, 2017)
The blindsnake genus Anilios (formerly Ramphotyphlops) is the largest and most diverse genus of snakes in Australia with 45 currently recognized species. Recent molecular genetic studies of the genus have identified high levels of cryptic diversity within many taxa, suggesting true species diversity is greatly underestimated. Anilios leptosoma is a slender blindsnake endemic to the mid-west of Western Australia. Although morphological variation has been identified within the species in the past, the systematics and true diversity remained unstudied. Here we use recent molecular data to guide a reappraisal of morphology in order to provide a taxonomic revision of the A. leptosoma species complex. We redescribe A. leptosoma and describe two new species that occur to the south of most of true A. leptosoma’s distribution: A. systenos sp. nov. and A. obtusifrons sp. nov. Anilios systenos sp. nov. is known from the Geraldton region with the furthest record only 100 km to the north-east, a very small range for a species of snake. Anilios obtusifrons sp. nov. has an even smaller distribution, as it is only known from a small coastal area south of Kalbarri and may represent a range-restricted taxa. All species are genetically divergent from each other and can be distinguished by consistent morphological characteristics, including the shape of the snout, the termination point of the rostral cleft and number of mid-body scale rows and ventral scales.